COMPARATIVE STUDY OF KNOWLEDGE AND SOCIAL ENVIRONMENT FOR ADOLESCENTS WHICH INFORMATION PROGRAMS AND TEENAGER COUNSELING ABOUT EARLY MARRIAGE IN STATE HIGH SCHOOLS IN KONAWE KEPULAUAN DISTRICT: EARLY MARRIAGE - Jumriah Abdullah; Tasnim Tasnim; La Banudi (STIKes Mandala Waluya Kendari, 2021)
Background:Based on data from the Central Statistics Agency of Konawe Islands Regency in 2019, it is known that the number of Senior High Schools is 7 units, with a total of 1,717 students. The results of reports of teenagers who married before the age of 18 in 2019 were as many as 49 people. Based on this, the rate of early marriage in the last 2 years actually shows an increase. Researchers took the theme of early marriage because from the results of preliminary studies conducted by researchers, most adolescents have insufficient knowledge about early marriage and its effects on the social environment of adolescents. So it is not surprising why the rate of early marriage in Konawe Islands Regency is generally the third highest in Southeast Sulawesi Province. Methods:This research is a quantitative research with a comparative study research type. The population in this study were 332 people and 179 samples with the sampling technique using stratified random sampling. Result:Test results with the Mann Whitney Test The significant value for knowledge shows the value of p-value = 0.000 <value ? = 0.05 and the significant value for the social environment of adolescents shows the value of pvalue = 0.000 <value ? = 0.05, which means that there are differences in knowledge and social environment of adolescents in State Senior High School the Youth Counseling Program and Information are active and inactive towards early marriage. Conclusion:There are differences in the knowledge and social environment of adolescents in the State MenengaAtas School where the Youth Counseling Program and Information are active and inactive towards early marriage.